(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
What is the genre of essay in this work? What is the essence of this genre. Brief information is given about the directions of the essays and their essence, as well as about the Uzbek ADIBS who created in the genre of the essay and their works.